2010
DOI: 10.1007/s10484-010-9128-8
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Vagal Tone: A Possible Mechanism for Functional Abdominal Pain

Abstract: Functional abdominal pain (FAP) causes disruption of daily activities/missed school days, over utilization of healthcare, unnecessary surgeries, and anxiety in 10-15% of children. Its etiology is not clearly understood, however the success of several clinical protocols suggests that autonomic dysregulation is a factor. In this study autonomic activity, including heart rate variability (HRV), was compared between children with FAP and a comparison group. Twenty children with FAP and 10 children without FAP betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 45 publications
2
54
0
3
Order By: Relevance
“…For example, increasing vagal tone through biofeedback decreases functional abdominal pain symptoms in children 25 . Heart rate variability analysis in our patient sample confirms the presence of reduced cardiac vagal tone in all CPP groups, greatest in the IC/BPS group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing vagal tone through biofeedback decreases functional abdominal pain symptoms in children 25 . Heart rate variability analysis in our patient sample confirms the presence of reduced cardiac vagal tone in all CPP groups, greatest in the IC/BPS group.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies shows HRV BFB's potential for treating a variety of physical and mental disorders, including depression (Karavidas et al, 2007; Siepmann et al, 2008; Zucker et al, 2009), post-traumatic stress disorder (Tan, Dao, Farmer, Sutherland, & Gevirtz, 2011; Zucker et al, 2009), various anxiety disorders and stress symptoms (Henriques, Keffer, Abrahamson, & Horst, 2011; McCraty, Atkinson, Lipsenthal, & Arguelles, 2009; Nolan et al, 2005; Zucker et al, 2009), food craving (Meule, Freund, Skirde, Vögele, & Kübler, 2012), hypertension (Lin et al, 2012; McCraty et al, 2009; Nolan et al, 2005), chronic pain (Hallman, Olsson, von Schéele, Melin, & Lyskov, 2011; Hassett et al, 2007; Sowder, Gevirtz, Shapiro, & Ebert, 2010), asthma (Lehrer, Smetankin, & Potapova, 2000; Lehrer et al, 2004) and heart disease (Nolan et al, 2005). HRV BFB has also been shown to reduce symptom severity and improve quality of life for individuals with chronic obstructive pulmonary disease (Giardino, Chan, & Borson, 2004), and heart failure (Moravec, 2008), as well as for individuals reporting medically unexplained symptoms (Katsamanis et al, 2011).…”
Section: Hrv Bfb An Overviewmentioning
confidence: 99%
“…However, research has shown that a person can, in fact, control this part of the nervous system when provided with appropriate feedback of its functioning [70]. In pediatric gastroenterology, mind–body research suggests that biofeedback may be helpful in treating symptoms of IBS and functional abdominal pain (FAP) such as dyspepsia, bloating, and cramping [71,72]. …”
Section: Mind–body Interventionsmentioning
confidence: 99%
“…A study by Sowder et al [72] investigated the effect of HRVB in children with FAP. Children participated in six sessions of HRVB aimed at normalizing autonomic balance.…”
Section: Mind–body Interventionsmentioning
confidence: 99%